2021
DOI: 10.3390/jcm10132939
|View full text |Cite
|
Sign up to set email alerts
|

First Evaluation of a New Dynamic Scoring System Intended to Support Prescription of Adjuvant CytoSorb Hemoadsorption Therapy in Patients with Septic Shock

Abstract: Introduction: Despite advances in critical care medicine, adjunctive approaches in sepsis therapy have failed to prove their efficacy. Notwithstanding promising results using hemoadsorption (CytoSorb), questions remain concerning timing and dosing. We created a dynamic scoring system (DSS) to assess patients with early septic shock and performed a first evaluation of the system in this patient population. Methods: Data from 502 patients with septic shock according to Sepsis-3 criteria were retrospectively anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Although a direct comparison between CytoSorb-treated patients and controls was not reported, improved survival was observed in the CytoSorb group in patients who initiated CytoSorb hemoadsorption earlier (≤12 h vs. >24 h, p = 0.037). However, CytoSorb therapy was not associated with 56-day survival ( p = 0.095) in a multivariable analysis of a subset of patients who received CytoSorb or CRRT and standard care [ 86 ]. Finally, CytoSorb therapy was not associated with improved survival in a recent meta-analysis assessing the effect of different extracorporeal blood purification techniques on mortality in patients with sepsis [ 87 ].…”
Section: Hemoadsorptionmentioning
confidence: 99%
“…Although a direct comparison between CytoSorb-treated patients and controls was not reported, improved survival was observed in the CytoSorb group in patients who initiated CytoSorb hemoadsorption earlier (≤12 h vs. >24 h, p = 0.037). However, CytoSorb therapy was not associated with 56-day survival ( p = 0.095) in a multivariable analysis of a subset of patients who received CytoSorb or CRRT and standard care [ 86 ]. Finally, CytoSorb therapy was not associated with improved survival in a recent meta-analysis assessing the effect of different extracorporeal blood purification techniques on mortality in patients with sepsis [ 87 ].…”
Section: Hemoadsorptionmentioning
confidence: 99%
“…85 h), is associated with lower mortality [ 72 ]. More retrospective studies demonstrated a mortality benefit for hemoadsorption [ 81 ], especially if CytoSorb ® therapy was started early (within 12 h) [ 82 ]. On the other hand, several recently published studies have failed to demonstrate any effect of hemoadsorption on mortality [ 74 , 83 ].…”
Section: Hemoadsorption With Cytosorb ®mentioning
confidence: 99%
“…On the other hand, it remains undetermined which patients, if any, could potentially benefit from such a therapy. Possibly, a recently presented dynamic scoring system may be useful to help identifying the right patients [ 82 ]. None of these have been scrutinized by adequately powered randomized controlled trials.…”
Section: Perspectivesmentioning
confidence: 99%
“…With great interest we read the article by Klaus Kogelmann and co-authors on the "First Evaluation of a New Dynamic Scoring System Intended to Support Prescription of Adjuvant CytoSorb Hemoadsorption Therapy in Patients with Septic Shock" [1]. The authors report interesting data from a retrospective evaluation of 502 patients in septic shock treated in four centers in Germany; 198 of these patients received adjunctive CytoSorb treatment.…”
mentioning
confidence: 99%